2020
DOI: 10.1136/rapm-2019-101262
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cannabinoid receptor 2 activation reduces hypersensitivity associated with bone cancer pain and improves the integrity of the blood–spinal cord barrier

Abstract: BackgroundDisruption of the blood–spinal cord barrier (BSCB) can facilitate inflammation that results in pain hypersensitivity. Proinflammatory cytokines produced by activated microglia and astrocytes damage the BSCB. This study aims to explore whether the BSCB is damaged in the bone cancer pain (BCP) model and to investigate a potential role and mechanism of JWH015 ((2-methyl-1-propyl-1H-indol-3-yl)−1-naphthalenylmethanone), a selective cannabinoid receptor 2 (CB2R) agonist, in preserving the BSCB integrity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Bone cancer pain (BCP) is a chronic pain and a severe complication of malignancy that is characterized by hyperalgesia and allodynia (Buga & Sarria, 2012;Wang et al, 2020). Previous studies have shown that BCP occurs in approximately 21% of the cancer patients who die of cancer, which severely affects the quality of life in these patients and increases the social burden (Kane et al, 2015;Turabi & Plunkett, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bone cancer pain (BCP) is a chronic pain and a severe complication of malignancy that is characterized by hyperalgesia and allodynia (Buga & Sarria, 2012;Wang et al, 2020). Previous studies have shown that BCP occurs in approximately 21% of the cancer patients who die of cancer, which severely affects the quality of life in these patients and increases the social burden (Kane et al, 2015;Turabi & Plunkett, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of low back and leg pain involves mixed components of neuropathic and nociceptive mechanisms [ 25 ]. Spinal neuropathic pain is related to increased levels of inflammatory cytokines and disrupted and increased permeability of the blood–spinal barrier, originally composed of tight junctions of capillary endothelial cell surrounded by lamina [ 26 ]. Dysfunction and breakage of the blood–spinal cord barrier is observed in several neurodegenerative disorders, peripheral neural injury-induced inflammatory pain, and chemotherapy-induced neuropathic pain [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal neuropathic pain is related to increased levels of inflammatory cytokines and disrupted and increased permeability of the blood–spinal barrier, originally composed of tight junctions of capillary endothelial cell surrounded by lamina [ 26 ]. Dysfunction and breakage of the blood–spinal cord barrier is observed in several neurodegenerative disorders, peripheral neural injury-induced inflammatory pain, and chemotherapy-induced neuropathic pain [ 26 , 27 ]. In a rat sciatic nerve model, recruitment of inflammatory materials outside the nerve led to damage of the epineurium and depletion of epineural adipocytes [ 21 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury (SCI) often leads to permanent loss of limb function defect due to disruption of the BSCB and the ensuing secondary injuries [35,36]. The BSCB is a semi-permeable interface of blood vessels that surrounds the spinal cord, and consists of the basement membrane, endothelial cells, pericytes, and astrocytes endplate foot processes [37]. The BSCB protects the spinal cord microenvironment from both endogenous and exogenous factors [38,39].…”
Section: Discussionmentioning
confidence: 99%